Children's Literature Collections
X, 261 p.
Keywords: This book provides scholars, both national and international, with a basis for advanced research in children’s literature in collections. Examining books for children published across five centuries, gathered from the collections in Dublin, this unique volume advances causes in collecting, librarianship, education, and children’s literature studies more generally. It facilitates processes of discovery and recovery that present various pathways for researchers with diverse interests in children’s books to engage with collections. From book histories, through bookselling, information on collectors, and histories of education to close text analyses, it is evident that there are various approaches to researching collections. In this volume, three dominant approaches emerge: history and canonicity, author and text, ideals and institutions. Through its focus on varied materials, from fiction to textbooks, this volume illuminates how cities can articulate a vision of children's literature through particular collections and institutional practices. .